The AGN Nature of LINER Nuclear Sources - Márquez, Isabel; Masegosa, Josefa; González-Martin, Omaira; Hernández-Garcia, Lorena; Pović, Mirjana; Netzer, Hagai; Cazzoli, Sara; del Olmo, Ascensión (Frontiers in Astronomy and Space Sciences, 2017)
Low-ionization nuclear emission-line regions (LINERs) are specially interesting objects since not only they represent the most numerous local Active Galactic Nuclei population, but they could be the link between normal and active galaxies as suggested by their low X-ray luminosities. The origin of LINER nuclei being still controversial, our works, through a multiwavelength approach, have contributed, firstly, to confirm that a large number of nuclear LINERs in the local universe are AGN powered. Secondly, from the study of X-ray spectral variability, we found that long term variations are very common, and they are mostly related to hard energies (2-10 keV). These variations might be due to changes in the absorber and/or intrinsic variations of the source. Thirdly, Mid-infrared (MIR) imaging also indicates that LINERs are the low luminosity end of AGN towards lower luminosities, and MIR spectroscopy shows that the average spectrum of AGN-dominated LINERs with X-ray luminosities L$_X$(2-10 keV) $>$ 10$^{41}$ erg/s is similar to the average mid-IR spectrum of AGN-dominated Seyfert 2s; for fainter LINERS, their spectral shape suggests that the dusty-torus may disappear. Fourth, the extended H$α$ emission of LINERs at HST resolution indicates that they follow remarkably well the Narrow Line Region morphology and the luminosity-size relation obtained for Seyfert and QSOs; HST H$α$ morphology may suggest the presence of outflows, which could contribute to the line broadening, with the resulting consequences on the percentage of LINERs where the Broad Line Region is detected. This issue is being revisited by our group with a high spectral resolution set of optical data for nearby type-1 LINERs. Finally, concerning systematic studies on the role of star formation in LINERs, which are scarce, our contribution deals with the study of a sample of the most luminous, highest star formation rate LINERs in the local Universe (at z from 0.04 to 0.11), together with its comparison with both lower-redshift LINERs and luminous LINERs previously detected at z $\sim$ 0.3. Most of our sources have L$_{AGN}$ $\sim$ L$_{SF}$, suggesting co-evolution of black hole and stellar mass. The AGN luminosity of local LINERs generally is related to the position they occupy on